The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.4028/www.scientific.net/amr.10.89
|View full text |Cite
|
Sign up to set email alerts
|

Joining by Forming of Lightweight Frame Structures

Abstract: Joining of lightweight frame structures in small quantities is subject to specific conditions, which are exemplarily determined for joining by forming processes. Experimental investigations have been carried out to evaluate both feasibility and capability of joining by forming processes. Joining has been accomplished by compressing or expanding cylindrical profiles using rigid tools for rolling-in processes, fluid active medium for hydro-forming as well as active energy for electromagnetic forming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The design of the groove should be based on the forming process [2]. axial loads primarily by a mechanical resistance against deformation of an undercut section.…”
Section: Form-fit Joiningmentioning
confidence: 99%
“…The design of the groove should be based on the forming process [2]. axial loads primarily by a mechanical resistance against deformation of an undercut section.…”
Section: Form-fit Joiningmentioning
confidence: 99%
“…Another opportunity for formability improvement was discussed in [26] where the blank was preformed into a shape which utilized formability of the adjacent portions of the blank to fill the corners of the die shape. Authors [27] demonstrated that EHF has a better capability to form sharp corners than quasistatic hydroforming described in [28] and also requires a lower clamping force employing the inertia of the tool and the clamping press, which requires a much smaller capital investment. A reconfigurable EHF tool comprising of several small size chambers can be assembled together for the forming of various shapes, as suggested by Golovashchenko [29].…”
Section: Introductionmentioning
confidence: 99%
“…Typical joining techniques that are used for these types of structures are laser welding, friction stir welding as well as joining by hydroforming and electromagnetic forming [14][15][16]. Certain alignment accuracy is necessary in order to apply these methods.…”
Section: Introductionmentioning
confidence: 99%